Histochemical evaluation of stromal components in fibrous dysplasia, central ossifying fibroma and juvenile ossifying fibroma affecting the jaw bones - MAHESHWARI, PARUL; Rao, Nirmala N; Radhakrishna, Raghu (International Journal of Dental Research, 2013)
Background: Oral Pathologists often come across fibro-osseous lesions involving the jaws with intersecting clinico-pathologic features which makes their diagnosis challenging. Due to the difference in their pathogenesis, the treatment varies and so does the prognosis which makes differentiation essential. Objectives: This study intended to evaluate the stromal components of fibrous dysplasias, central and juvenile ossifying fibromas affecting the jaw bones using histochemical stains and to determine the histological parameters important for their differentiation. Methods: Three sections each of forty-seven formalin-fixed decalcified paraffin-embedded tissues were stained with three special stains (Modified Tetrachrome, Modified Attwood’s and Potassium-monopersulfate aldehyde fuschin stain) and analysed for  morphology and structure of calcifications, osteoblastic rimming, cellularity and  vascularity of the stroma, collagen pattern and oxytalan fibers. Results: Despite the overlap in the histopathological features, few parameters were more pertinent to one lesion than the others. Fibrous dysplasia cases had characteristic thin curvilinear calcifications which were discontinuous whereas central and juvenile ossifying fibromas had broader calcifications which were interconnected. The structure of calcifications was mostly woven in fibrous dysplasia but few longstanding cases did show lamellar bone. The cellularity and vascularity was considerably higher in ossifying fibromas than fibrous dysplasia. Oxytalan fibers were more evident in cases of ossifying fibromas. Conclusion: Histopathological analysis alone may not suffice for the diagnosis of fibro-osseous lesions due to the apparent similarity, thus stressing on the importance of radiologic and genetic analysis in the diagnosis of fibro-osseous lesions.